Solution of higher order ODEs using backward difference method. - Suleiman, Mohamed; Ibrahim, Zarina Bibi; Rasedee, Ahmad Fadly Nurullah (Hindawi Publishing Corporation, 2011)
The current numerical technique for solving a system of higher-order ordinary differential equations (ODEs) is to reduce it to a system of first-order equations then solving it using first-order ODE methods. Here, we propose a method to solve higher-order ODEs directly. The formulae will be derived in terms of backward difference in a constant stepsize formulation. The method developed will be validated by solving some higher-order ODEs directly with constant stepsize. To simplify the evaluations of the integration coefficients, we find the relationship between various orders. The result presented confirmed our hypothesis.